Method for repairing retired lithium iron phosphate positive electrode black powder through low-temperature recrystallization, lithium iron phosphate positive electrode material and application of lithium iron phosphate positive electrode material
The low-temperature recrystallization repair method solves the problem of structural damage when repairing lithium iron phosphate cathode materials at high temperatures, achieves low-energy consumption, high-performance material regeneration, and improves the rate performance and cycle stability of the material.
Patent Information
- Application Number
- CN202310293016.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When the prior art repairs the retired lithium iron phosphate positive electrode material under high temperature environment, it is easy to cause material structure damage, low performance, and lack competitiveness.
Using low-temperature re-crystallization repair methods, the collected retired iron phosphate lithium and black powder are sieved, ball milling with lithium salt and carbon source, and then burned and quenched and cooled under the condition of 250 ° C-350 ° C to remove impurities and remove impurities and remove impurities and remove impurities. Implement the regeneration of materials.
It realizes the recrystallization of lithium iron phosphate materials to supplement lithium at low temperatures, reduces the occurrence of structural damage to active materials at high temperatures, has lower energy consumption and CO2 emissions, and at the same time improves the rate performance and cycle stability of the material.
Smart Images

Figure CN119349529A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of recycling retired lithium iron phosphate, and in particular to a method for low-temperature recrystallization repairing retired lithium iron phosphate positive electrode black powder, a lithium iron phosphate positive electrode material and an application thereof. Background Art
[0002] Retired lithium-ion batteries contain huge economic benefits, especially the waste positive electrodes usually contain a high proportion of transition metal elements. If these elements can be effectively recycled and reused, it can not only reduce environmental pollution but also create higher economic value. Traditional methods of recycling positive electrode materials are based on metallurgical technology (pyrometallurgy and hydrometallurgy), using waste positive electrodes as minerals for metal extraction. These high-cost and complex extraction methods can achieve good economic benefits for the recovery of high-value-added metals such as Ni / Co / Li, and their benefits can cover the high mining costs. However, the recycling of positive electrode materials based on cheap metal elements such as Fe is often overlooked, although these positive electrodes also occupy a huge market share. For LiFePO4 (LFP), it is crucial to develop efficient and low-cost direct regeneration technology.
[0003] Patent CN114243144 adds carbonate, phosphate or LiOH and other lithium sources to LFP black powder, and the lithium source reacts with the lithium-deficient phase in the retired black powder at high temperature to generate a new LFP phase, thereby directly repairing and regenerating the LFP black powder, thereby avoiding the problems of high energy consumption, high cost, and high pollution in metallurgical methods. However, high temperature environments often cause structural damage to the originally active LFP material, resulting in low performance and lack of competitiveness of the repaired LFP. How to directly repair the damaged positive electrode black powder structure without damaging the active LFP material is the key to direct repair and regeneration. Summary of the invention
[0004] The present invention is made to solve the above-mentioned problems, and aims to provide a method for low-temperature recrystallization repair of retired lithium iron phosphate positive electrode black powder, a lithium iron phosphate positive electrode material and its application.
[0005] The invention provides a method for repairing retired lithium iron phosphate positive electrode black powder by low-temperature recrystallization, which has the following characteristics and comprises the following steps: step 1, sieving the collected black powder of waste retired batteries containing lithium iron phosphate, removing large pieces of current collector aluminum strips in the black powder, reducing the content of metal Al single substance to below 1000ppm, and obtaining black powder with low Al content; step 2, adding the black powder with low Al content, lithium salt containing a certain amount of LiNO3, and carbon source into a ball mill for a period of time to obtain a ball milling mixture; step 3, placing the ball milling mixture into a muffle furnace and calcining it at 250°C-350°C, and obtaining a high-temperature calcined mixture after the heat preservation is completed; step 4, directly quenching and cooling the high-temperature calcined mixture, washing with water to remove impurities, filtering or centrifuging, and drying to obtain the repaired and regenerated lithium iron phosphate positive electrode material.
[0006] The method for low-temperature recrystallization repair of retired lithium iron phosphate positive electrode black powder provided by the present invention may also have the following characteristics: wherein, in step one, the collected retired battery black powder containing lithium iron phosphate is black powder obtained by mixing and crushing the graphite negative electrode and the lithium iron phosphate positive electrode of the retired battery, or is black powder obtained by crushing only the lithium iron phosphate positive electrode of the retired battery, and the retired battery is a retired energy storage battery or a power battery.
[0007] The method for low-temperature recrystallization repair of retired lithium iron phosphate positive electrode black powder provided by the present invention may also have the following characteristics: wherein, in step one, sieving is performed using a 150-mesh sieve.
[0008] In the method for low-temperature recrystallization repair of retired lithium iron phosphate positive electrode black powder provided by the present invention, it can also have the following characteristics: wherein, in step 2, the lithium salt includes only lithium nitrate, or the lithium salt includes lithium nitrate and non-lithium nitrate salt, the non-lithium nitrate salt is any one or more of lithium hydroxide, lithium carbonate and lithium acetate, the carbon source is any one or more of glucose, tannic acid, citric acid and starch, and the mass ratio of black powder with low Al content, lithium salt and carbon source is 10kg:(500g-700g):(300g-500g).
[0009] The method for low-temperature recrystallization repair of retired lithium iron phosphate positive electrode black powder provided by the present invention may also have the following characteristics: wherein, in step 2, the lithium salt includes lithium nitrate and non-nitrate lithium salt, and the mass ratio of lithium nitrate to non-nitrate lithium salt in the lithium salt is 1:6-5:1.
[0010] The method for low-temperature recrystallization repair of retired lithium iron phosphate positive electrode black powder provided by the present invention may also have the following characteristics: wherein, in step 2, the ball milling medium is any one of anhydrous ethanol, deionized water and acetone, the ball milling speed is 300rpm-800rpm, and the ball milling time is 30min-60min.
[0011] The method for low-temperature recrystallization repair of retired lithium iron phosphate positive electrode black powder provided by the present invention may also have the following characteristics: wherein, in step three, the ball-milled mixture is first dried, and then placed in a muffle furnace, and heated at a heating rate of 5°C / min to 300°C-350°C, and kept warm for 30min-60min.
[0012] The method for low-temperature recrystallization repair of retired lithium iron phosphate positive electrode black powder provided by the present invention may also have the following characteristics: wherein, in step four, quenching and cooling uses room temperature deionized water or a deionized ice-water mixture or liquid nitrogen, filtration is pressure filtration, and drying is drying or flash drying.
[0013] The present invention also provides a lithium iron phosphate positive electrode material obtained by utilizing the above-mentioned method for repairing retired lithium iron phosphate positive electrode black powder by low-temperature recrystallization.
[0014] The present invention also provides an application of the above-mentioned lithium iron phosphate positive electrode material, characterized in that: the application includes: adjusting the lithium iron phosphate positive electrode material to a required particle size through air flow grinding, and then using it as an active material to make a battery slurry in a ratio of active material: conductive agent: binder = 9:1:1, coating it on an aluminum current collector, and obtaining a positive electrode sheet after drying, which is assembled into a half-cell with a lithium metal negative electrode.
[0015] Functions and Effects of the Invention
[0016] According to the method of low-temperature recrystallization repairing retired lithium iron phosphate positive electrode black powder, lithium iron phosphate positive electrode material and application thereof involved in the present invention, because the method utilizes LiNO3 as a lithium source or one of the lithium sources, since LiNO3 has a high driving force for the lithium replenishing reaction with the lithium-deficient phase in the retired battery black powder containing lithium iron phosphate, the lithium replenishing reaction occurs at a relatively low temperature, thereby realizing lithium replenishment by low-temperature recrystallization, reducing the occurrence of structural destruction of active lithium iron phosphate materials at high temperatures, and having lower energy consumption and CO2 emissions.
[0017] In addition, because the method of the present invention adopts a quenching process, the recrystallized lithium iron phosphate grains are super nanocrystalline. These abundant grain boundaries can serve as fast transmission channels for lithium ions, thereby improving the rate performance and cycle stability of the repaired material. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a TEM image of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention;
[0019] Figure 2 is an XRD diagram of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention, compared with the untreated lithium iron phosphate black powder;
[0020] Figure 3It is the charge and discharge curve of the half-cell made of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention at a rate of 0.1C, comparing the commercial new lithium iron phosphate and the untreated lithium iron phosphate black powder;
[0021] Figure 4 The battery cycle curve of the half-cell made of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention at a rate of 1C is compared with commercial new lithium iron phosphate and untreated lithium iron phosphate black powder;
[0022] Figure 5 is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 2 of the present invention;
[0023] Figure 6 is the XRD pattern of the lithium iron phosphate positive electrode material prepared in Example 2 of the present invention;
[0024] Figure 7 is the charge and discharge curve of a half-cell made of the lithium iron phosphate positive electrode material prepared in Example 2 of the present invention at a rate of 0.1C;
[0025] Figure 8 is a battery cycle curve of a half-cell made of the lithium iron phosphate positive electrode material prepared in Example 2 of the present invention at a 1C rate;
[0026] Fig. 9 This is an electrochemical cycle diagram of a half-cell made of the lithium iron phosphate positive electrode material prepared in Example 3 of the present invention at a rate of 1C;
[0027] Fig.10 It is an electrochemical cycle diagram of a half-cell made of the lithium iron phosphate positive electrode material prepared in Example 4 of the present invention at a rate of 1C.
[0028] Fig.11 It is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 5 of the present invention.
[0029] Fig.12 It is an electrochemical cycle diagram of a half-cell made of the lithium iron phosphate positive electrode material prepared in Example 5 of the present invention at a rate of 1C. DETAILED DESCRIPTION
[0030] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the following embodiments, in conjunction with the accompanying drawings, specifically describe a method for low-temperature recrystallization repair of retired lithium iron phosphate positive electrode black powder, a lithium iron phosphate positive electrode material and its application.
[0031] <Example 1>
[0032] This embodiment provides a method for repairing retired lithium iron phosphate positive electrode black powder by low temperature recrystallization, characterized in that it includes the following steps:
[0033] Step 1: The black powder crushed from the dismantled lithium iron phosphate positive electrode sheets of retired power batteries is passed through a 150-mesh sieve to remove large pieces of current collector aluminum strips in the black powder, and the content of metal Al is reduced to below 1000 ppm to obtain black powder with a low Al content.
[0034] Step 2: add 10 kg of black powder with low Al content, 550 g of lithium nitrate and 300 g of sucrose into a ball mill, use anhydrous ethanol as the ball milling medium, rotate at 300 rpm, and perform ball milling for 30 minutes to obtain a ball milled mixture.
[0035] Step three, drying the ball-milled mixture in a vacuum oven at 100° C. for 6-12 h, then placing it in a muffle furnace and heating it at a heating rate of 5° C. / min to 320° C., and keeping the temperature for 30 min to obtain a high-temperature calcined mixture.
[0036] Step 4: directly put the high-temperature calcined mixture after the heat preservation into room temperature deionized water for cooling, stirring for 30 minutes, filtering out the solid, and flash drying to obtain the repaired and regenerated lithium iron phosphate positive electrode material.
[0037] Figure 1 is a TEM image of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention; Figure 2 1 is an XRD diagram of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention, compared with the untreated lithium iron phosphate black powder.
[0038] like Figure 1 and Figure 2 As shown in the figure, the particle size of the prepared lithium iron phosphate positive electrode material is ~100nm, which ensures the excellent electronic conductivity and lithium ion conductivity of the material, so that the material can show excellent rate performance; through phase analysis, it can be seen that the prepared lithium iron phosphate positive electrode material is a pure phase olivine structure without impurity phase. Compared with the unrepaired black powder raw material XRD, it can be seen that the FePO4, LiPO3, P4O 10 and Fe2O3 impurities all disappeared after being repaired and regenerated by LiNO3.
[0039] In addition, the lithium iron phosphate positive electrode material prepared by the above method can be crushed by air flow milling equipment to adjust its particle size distribution to the required particle size, such as commercial LFP level (D50~1.5um, D90~8um, D100~15um), and then used as an active material, and the battery slurry is made according to the ratio of active material: conductive agent (acetylene black): binder (PVDF) = 9:1:1, coated on the aluminum current collector, and dried to obtain the positive electrode sheet, which is assembled into a half-cell with a lithium metal negative electrode to test its electrochemical performance.
[0040] Figure 3 It is the charge and discharge curve of the half-cell made of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention at a rate of 0.1C, comparing the commercial new lithium iron phosphate and the untreated lithium iron phosphate black powder; Figure 4 It is a battery cycle curve of a half-cell made of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention at a rate of 1C, comparing commercial new lithium iron phosphate and untreated lithium iron phosphate black powder.
[0041] like Figure 3 As shown, the lithium iron phosphate cathode material prepared in this embodiment exhibits excellent discharge capacity, with a discharge capacity of 162 mAh / g at a rate of 0.1C. Compared with the purchased commercial lithium iron phosphate new material (discharge capacity of about 159 mAh / g at a rate of 0.1C), it has a slight advantage in terms of gram capacity. Compared with the unrepaired black powder raw material (discharge capacity of about 134 mAh / g at a rate of 0.1C), the capacity is greatly improved after LiNO3 repair and regeneration. Figure 4 As shown, the lithium iron phosphate positive electrode material prepared in this embodiment has excellent cycle stability. After 500 charge and discharge cycles at a 1C rate, the capacity retention rate is about 90%.
[0042] <Example 2>
[0043] This embodiment provides a method for repairing retired lithium iron phosphate positive electrode black powder by low temperature recrystallization, characterized in that it includes the following steps:
[0044] Step 1: The black powder obtained by mixing and crushing the graphite negative electrode and the lithium iron phosphate positive electrode of the retired power battery is passed through a 150-mesh sieve to remove large pieces of current collector aluminum strips in the black powder, and the content of the metal Al element is reduced to below 1000 ppm to obtain black powder with a low Al content.
[0045] Step 2: add 10 kg of black powder with low Al content, 500 g of lithium nitrate, 100 g of lithium carbonate, and 300 g of sucrose into a ball mill, use deionized water as the ball milling medium, rotate at 300 rpm, and perform ball milling for 30 minutes to obtain a ball milled mixture.
[0046] Step three, spray drying the ball-milled mixture, with the inlet air temperature of the spray drying being 230°C and the outlet air temperature being 90°C, to obtain a dry mixed powder with a moisture content of less than 1%; then placing the mixture in a muffle furnace and heating it at a heating rate of 5°C / min to 320°C, keeping the temperature for 30 minutes, to obtain a high-temperature calcined mixture.
[0047] Step 4: directly put the high-temperature calcined mixture after the insulation into deionized water at room temperature for cooling, stirring for 30 minutes, centrifuging and re-selecting to separate the graphite negative electrode and the lithium iron phosphate positive electrode, and drying to obtain the repaired and regenerated lithium iron phosphate positive electrode material.
[0048] Figure 5 is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 2 of the present invention; Figure 6 It is the XRD diagram of the lithium iron phosphate positive electrode material prepared in Example 2 of the present invention.
[0049] like Figure 5 and Figure 6 As shown, the particle size of the prepared lithium iron phosphate positive electrode material is ~300nm, ensuring that the material is not limited by the conduction of electrons and ions, so the material can exhibit excellent rate performance; through phase analysis, it can be seen that the prepared lithium iron phosphate positive electrode material is a pure phase olivine structure and does not contain impurity phases.
[0050] In addition, the lithium iron phosphate positive electrode material prepared by the above method can be crushed by air flow milling equipment to adjust its particle size distribution to the required particle size, such as commercial LFP level (D50~1.5um, D90~8um, D100~15um), and then used as an active material, and the battery slurry is made according to the ratio of active material: conductive agent (acetylene black): binder (PVDF) = 9:1:1, coated on the aluminum current collector, and dried to obtain the positive electrode sheet, which is assembled into a half-cell with a lithium metal negative electrode to test its electrochemical performance.
[0051] Figure 7 is the charge and discharge curve of a half-cell made of the lithium iron phosphate positive electrode material prepared in Example 2 of the present invention at a rate of 0.1C; Figure 8 It is a battery cycle curve of a half-cell made of the lithium iron phosphate positive electrode material prepared in Example 2 of the present invention at a 1C rate.
[0052] like Figure 7 As shown, the lithium iron phosphate positive electrode material prepared in this embodiment exhibits excellent discharge capacity, and the discharge specific capacity at a rate of 0.1C reaches 163 mAh / g. Figure 8 As shown, the lithium iron phosphate positive electrode material prepared in this embodiment has excellent cycle stability. After 1000 charge and discharge cycles at a 1C rate, the capacity retention rate is higher than 95%.
[0053] <Example 3>
[0054] This embodiment provides a method for repairing retired lithium iron phosphate positive electrode black powder by low temperature recrystallization, characterized in that it includes the following steps:
[0055] Step 1: The black powder of the lithium iron phosphate positive electrode of the retired energy storage battery is crushed through a 150-mesh sieve to remove large pieces of current collector aluminum strips in the black powder, and the content of the metal Al single substance is reduced to below 1000 ppm to obtain black powder with a low Al content.
[0056] Step 2: Add 10 kg of black powder with low Al content, 400 g of lithium nitrate, 300 g of lithium hydroxide and 300 g of glucose into a nano ball mill, use deionized water as the ball milling medium, rotate at 700 rpm, and perform ball milling for 60 minutes to obtain a spheroidal graphite mixture.
[0057] Step three, spray-drying the ball-milled mixture to obtain a precursor material, and placing the precursor material in a muffle furnace to heat it up at a heating rate of 5°C / min to 300°C, and keeping the temperature for 45 minutes to obtain a high-temperature calcined mixture.
[0058] Step 4: directly put the high-temperature calcined mixture after the insulation into a room-temperature deionized ice-water mixture for quenching and cooling, stirring for 30 minutes, filtering to obtain a lithium iron phosphate material filter cake, flash drying, and obtaining a repaired and regenerated lithium iron phosphate positive electrode material.
[0059] In addition, the lithium iron phosphate positive electrode material prepared by the above method can be crushed by air flow milling equipment to adjust its particle size distribution to the required particle size, such as commercial LFP level (D50~1.5um, D90~8um, D100~15um), and then used as an active material, and the battery slurry is made according to the ratio of active material: conductive agent (acetylene black): binder (PVDF) = 9:1:1, coated on the aluminum current collector, and dried to obtain the positive electrode sheet, which is assembled into a half-cell with a lithium metal negative electrode to test its electrochemical performance.
[0060] Fig. 9 It is an electrochemical cycle diagram of a half-cell made of the lithium iron phosphate positive electrode material prepared in Example 3 of the present invention at a rate of 1C.
[0061] like Fig. 9 As shown, the lithium iron phosphate positive electrode material prepared in this embodiment has excellent cycle stability. After 1000 cycles at a rate of 1C, the capacity retention rate is about 96%, and the material exhibits a high discharge capacity and excellent rate performance.
[0062] <Example 4>
[0063] This embodiment provides a method for repairing retired lithium iron phosphate positive electrode black powder by low temperature recrystallization, characterized in that it includes the following steps:
[0064] Step 1: The black powder of the lithium iron phosphate positive electrode of the retired energy storage battery is crushed through a 150-mesh sieve to remove large pieces of current collector aluminum strips in the black powder, and the content of the metal Al single substance is reduced to below 1000 ppm to obtain black powder with a low Al content.
[0065] Step 2: Add 10 kg of black powder with low Al content, 100 g of lithium nitrate, 600 g of lithium acetate, and 500 g of starch into a ball mill, use acetone as the ball milling medium, rotate at 400 rpm, and ball mill for 25 minutes to obtain a spheroidal graphite mixture.
[0066] Step three, drying the acetone in the ball mill mixture, and then placing it in a muffle furnace and heating it at a heating rate of 5°C / min to 350°C, and keeping it warm for 60 minutes to obtain a high-temperature calcined mixture.
[0067] Step 4, adding the high-temperature calcined mixture after the insulation to liquid nitrogen for quenching and cooling, then adding it to deionized water and stirring for 30 minutes, separating the concentrate rich in lithium iron phosphate positive electrode material by centrifugation, and flash drying it to obtain the repaired and regenerated lithium iron phosphate positive electrode material.
[0068] In addition, the lithium iron phosphate positive electrode material prepared by the above method can be crushed by air flow milling equipment to adjust its particle size distribution to the required particle size, such as commercial LFP level (D50~1.5um, D90~8um, D100~15um), and then used as an active material, and the battery slurry is made according to the ratio of active material: conductive agent (acetylene black): binder (PVDF) = 9:1:1, coated on the aluminum current collector, and dried to obtain the positive electrode sheet, which is assembled into a half-cell with a lithium metal negative electrode to test its electrochemical performance.
[0069] Fig.10 It is an electrochemical cycle diagram of a half-cell made of the lithium iron phosphate positive electrode material prepared in Example 4 of the present invention at a rate of 1C.
[0070] like Fig.10 As shown, the lithium iron phosphate positive electrode material prepared in this embodiment has excellent cycle stability. After 1000 cycles at a rate of 1C, the capacity retention rate is about 95%, and the material exhibits a high discharge capacity and excellent rate performance.
[0071] <Example 5>
[0072] This embodiment provides a method for repairing retired lithium iron phosphate positive electrode black powder by low temperature recrystallization, characterized in that it includes the following steps:
[0073] Step 1: The black powder obtained by mixing and crushing the graphite negative electrode and the lithium iron phosphate positive electrode of the retired energy storage battery is passed through a 150-mesh sieve to remove large pieces of current collector aluminum strips in the black powder, and the content of the metal Al single substance is reduced to below 1000 ppm to obtain black powder with a low Al content.
[0074] Step 2: add 10 kg of black powder with low Al content, 500 g of lithium nitrate, 100 g of lithium carbonate, and 300 g of sucrose into a ball mill, use anhydrous ethanol as a ball milling medium, rotate at 300 rpm, and perform ball milling for 30 minutes to obtain a ball milled mixture.
[0075] Step three, drying the ball-milled mixture in a vacuum oven at 100° C. for 6-12 h, then placing it in a muffle furnace and heating it at a heating rate of 5° C. / min to 320° C., and keeping the temperature for 30 min to obtain a high-temperature calcined mixture.
[0076] Step 4: After the heat preservation, the high-temperature calcined mixture is naturally cooled in the furnace, and the graphite negative electrode and the lithium iron phosphate positive electrode are separated by centrifugal gravity separation, and then dried to obtain the repaired and regenerated lithium iron phosphate positive electrode material.
[0077] Fig.11 is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention;
[0078] like Fig.11 As shown, the particle size of the prepared lithium iron phosphate positive electrode material is ~800nm, which is larger than that of the quenched sample and the unquenched sample, resulting in limited electron and ion conductivity of the material, which is not conducive to the performance of rate performance.
[0079] In addition, the lithium iron phosphate positive electrode material prepared by the above method can be crushed by air flow milling equipment to adjust its particle size distribution to the required particle size, such as commercial LFP level (D50~1.5um, D90~8um, D100~15um), and then used as an active material, and the battery slurry is made according to the ratio of active material: conductive agent (acetylene black): binder (PVDF) = 9:1:1, coated on the aluminum current collector, and dried to obtain the positive electrode sheet, which is assembled into a half-cell with a lithium metal negative electrode to test its electrochemical performance.
[0080] Fig.12 It is a battery cycle curve of a half-cell made of the lithium iron phosphate positive electrode material prepared in Example 5 of the present invention at a 1C rate.
[0081] like Fig.12 As shown, the lithium iron phosphate positive electrode material prepared in this embodiment has excellent cycle stability. After 1000 charge and discharge cycles at a 1C rate, the capacity retention rate is about 90%.
[0082] The above-mentioned embodiments are preferred examples of the present invention and are not intended to limit the protection scope of the present invention.
Claims
1. A method for repairing retired lithium iron phosphate positive electrode black powder by low temperature recrystallization, characterized in that: The following steps are involved: Step 1: sieve the collected retired battery black powder containing lithium iron phosphate to remove large pieces of current collector aluminum strips in the black powder, reduce the content of metal Al to below 1000ppm, and obtain black powder with low Al content; Step 2, adding the black powder with low Al content, a lithium salt containing a certain amount of LiNO3, and a carbon source into a ball mill and ball milling for a period of time to obtain a ball milled mixture; Step 3, placing the ball-milled mixture into a muffle furnace and calcining at 250° C.-350° C., and after the heat preservation is completed, a high-temperature calcined mixture is obtained; Step 4: directly quench and cool the high-temperature calcined mixture, wash with water to remove impurities, filter or centrifuge, and then dry to obtain a repaired and regenerated lithium iron phosphate positive electrode material.
2. The method for repairing retired lithium iron phosphate positive electrode black powder by low temperature recrystallization according to claim 1, characterized in that: in, In step 1, the collected retired battery black powder containing lithium iron phosphate is a mixture of graphite negative electrodes and lithium iron phosphate positive electrodes of retired batteries, or is a mixture of only lithium iron phosphate positive electrodes of retired batteries. The retired battery is a retired energy storage battery or a power battery.
3. The method for repairing retired lithium iron phosphate positive electrode black powder by low temperature recrystallization according to claim 1, characterized in that: in, In step 1, the sieving is performed using a 150-mesh sieve.
4. The method for repairing retired lithium iron phosphate positive electrode black powder by low temperature recrystallization according to claim 1, characterized in that: in, In step 2, the lithium salt includes only lithium nitrate, or the lithium salt includes lithium nitrate and non-nitrate lithium salt, and the non-nitrate lithium salt is any one or more of lithium hydroxide, lithium carbonate and lithium acetate. The carbon source is any one or more of glucose, tannic acid, citric acid and starch. The mass ratio of the black powder with low Al content, the composite lithium salt and the carbon source is 10kg:(500g-700g):(300g-500g).
5. The method for repairing retired lithium iron phosphate positive electrode black powder by low temperature recrystallization according to claim 4, characterized in that: in, In step 2, the lithium salt includes lithium nitrate and non-nitrate lithium salt, and the mass ratio of lithium nitrate to non-nitrate lithium salt in the lithium salt is 1:6-5:
1.
6. The method for repairing retired lithium iron phosphate positive electrode black powder by low temperature recrystallization according to claim 1, characterized in that: in, In step 2, the ball milling medium is any one of anhydrous ethanol, deionized water and acetone, the ball milling speed is 300rpm-800rpm, and the ball milling time is 30min-60min.
7. The method for repairing retired lithium iron phosphate positive electrode black powder by low temperature recrystallization according to claim 1, characterized in that: in, In step three, the ball-milled mixture is first dried, and then placed in a muffle furnace, and heated at a heating rate of 5° C. / min to 300° C.-350° C., and kept warm for 30 min-60 min.
8. The method for repairing retired lithium iron phosphate positive electrode black powder by low temperature recrystallization according to claim 1, characterized in that: in, In step 4, the quenching cooling uses room temperature deionized water or a deionized ice water mixture or liquid nitrogen. The filtration is filter pressing, The drying is oven drying or flash drying.
9. A lithium iron phosphate positive electrode material prepared by the method for repairing retired lithium iron phosphate positive electrode black powder by low temperature recrystallization according to any one of claims 1 to 8.
10. The use of the lithium iron phosphate positive electrode material according to claim 9, characterized in that: The application includes: adjusting the lithium iron phosphate positive electrode material to a required particle size through air flow grinding, and then using it as an active material to make a battery slurry in a ratio of active material: conductive agent: binder = 9:1:1, coating it on an aluminum current collector, and obtaining a positive electrode sheet after drying, which is assembled into a half-battery with a lithium metal negative electrode.
Citation Information
Cited By
Method for synergistically supplementing lithium and phosphorus to directionally repair and regenerate lithium iron phosphate positive electrode material
CN121306922A
Method for recovering aluminum residue with controlled particle size, and use thereof
US12763390B2